Ответ:
Объяснение:
№1
1) -4;-3;-3;-1;0;1
2) -4;-3;-2;-1;0;1;2;3
№2
1) 7x > 14
x >![\frac{14}{7} \frac{14}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B14%7D%7B7%7D)
x > 2
2) -3x ≥ 12
x ≤ ![-\frac{12}{3} -\frac{12}{3}](https://tex.z-dn.net/?f=-%5Cfrac%7B12%7D%7B3%7D)
x ≤ — 4
3) 7x + 3 ≤ 30 - 2x;
9x ≤ 27
x ≤
= 3
4) 5,4 - 1,5x ≥ 0,3x - 3,6
1,8x ≤ 9
x ≤ 5
№3
1)
-5} \atop {x < - 2}} \right." alt="\left \{ {{x > -5} \atop {x < - 2}} \right." align="absmiddle" class="latex-formula">
2)
x^{2} +6 }} \right." alt="\left \{ {{8x+6< 3x+6+2x-2} \atop {x^{2}-8x-2>x^{2} +6 }} \right." align="absmiddle" class="latex-formula">
x^{2} +6 }} \right." alt="\left \{{{3x<2} \atop {x^{2}-8x-2-4+4>x^{2} +6 }} \right." align="absmiddle" class="latex-formula">
x^{2} +6 -x^{2} -6 }} \right." alt="\left \{{{x<-\frac{2}{3} } \atop {-8x+4>x^{2} +6 -x^{2} -6 }} \right." align="absmiddle" class="latex-formula">
-4}} \right." alt="\left \{{{x<-\frac{2}{3} } \atop {-8x> -4}} \right." align="absmiddle" class="latex-formula">
![\left \{{{x<-\frac{2}{3} } \atop {8x<4}} \right. \left \{{{x<-\frac{2}{3} } \atop {8x<4}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%7B%7Bx%3C-%5Cfrac%7B2%7D%7B3%7D%20%7D%20%5Catop%20%7B8x%3C4%7D%7D%20%5Cright.)
![\left \{{{x<-\frac{2}{3} } \atop {x<2}} \right. \left \{{{x<-\frac{2}{3} } \atop {x<2}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%7B%7Bx%3C-%5Cfrac%7B2%7D%7B3%7D%20%7D%20%5Catop%20%7Bx%3C2%7D%7D%20%5Cright.)
x є (-∞ ;
)